1988
DOI: 10.1002/dc.2840040218
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration of spleen: Diagnosis of a solitary ovarian metastasis

Abstract: We report a patient in whom a solitary splenic lesion detected by computed tomography (CT) was successfully diagnosed by fine-needle aspiration biopsy under CT guidance. The ability to distinguish metastatic carcinoma from lymphoma in the spleen assisted the clinician in making therapeutic decisions. Fine-needle aspiration of spleen is a reasonable diagnostic approach that has been underutilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Based on our evaluation, only 22 cases fulfi lled the criteria of "recurrence," "solitary," and "parenchymal." [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and these are summarized in Table 1. Most of the patients had stage III disease (FIGO classifi cation) and all underwent optimal tumor debulking, defi ned as the diameter of the largest residual tumor nodule measuring <2 cm at the end of the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our evaluation, only 22 cases fulfi lled the criteria of "recurrence," "solitary," and "parenchymal." [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and these are summarized in Table 1. Most of the patients had stage III disease (FIGO classifi cation) and all underwent optimal tumor debulking, defi ned as the diameter of the largest residual tumor nodule measuring <2 cm at the end of the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 22 cases of isolated parenchymal splenic recurrence have been reported. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] We report two further cases of splenic metastasis as the fi rst site of recurrence of ovarian cancer and review the literature on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the case reports the patients presented with nonspecific symptoms, and in 2 cases the symptoms were suggestive of lymphoma [7,9]. In cases where the diagnosis is in question, CT-guidcd fine-needle aspiration has been successfully utilized for preoperative diagnosis [12], This can be particularly use ful when lymphoma is high in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few case reports in the literature describing solitary carcinomatous metastases to the spleen. We have found a total of 13 cases described, 8 of which were gynecologic malignancies [6][7][8][9][10][11][12]. The other tumors included breast, lung and melano ma [10,13,14],…”
Section: Discussionmentioning
confidence: 99%
“…A final diagnosis could, thus, only be obtained through postoperative pathological investigation. Some authors reported that a fine-needle aspiration biopsy was a safe and valuable diagnostic tool for evaluating splenic lesions in oncologic patients [16, 17, 18, 19, 20, 21, 22]. However, the biopsy of the spleen is rarely attempted because of the possibility of hemorrhage, the fear of spillage of tumor cells, and the preconceived notion that the biopsy will not be of diagnostic help.…”
Section: Discussionmentioning
confidence: 99%